2011
DOI: 10.1186/1746-6148-7-64
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of experimental porcine circovirus type 1 infections in mid-gestational porcine foetuses

Abstract: BackgroundPorcine circovirus type 1 (PCV1) has been described as a non-cytopathic contaminant of the PK-15 cell line. Several experimental infections with PCV1 failed to reproduce disease in pigs. Therefore, PCV1 is generally accepted as non-pathogenic to pigs. To our knowledge, nothing is known about the outcome of PCV1 infections in porcine foetuses. This was examined in the present study.ResultsNine foetuses from three sows were inoculated at 55 days of gestation: three with 104.3 TCID50 of the PCV1 cell cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…How PCV2 is involved in the pathogenesis of PCVDs remains unclear. Koch's postulates establishing PCV2 as the causative agent have been partially satisfied for only PCV2-SD and PCV2-RD (Ellis and others 1998, Krakowka and others 2001, Saha and others 2011). …”
Section: Introductionmentioning
confidence: 99%
“…How PCV2 is involved in the pathogenesis of PCVDs remains unclear. Koch's postulates establishing PCV2 as the causative agent have been partially satisfied for only PCV2-SD and PCV2-RD (Ellis and others 1998, Krakowka and others 2001, Saha and others 2011). …”
Section: Introductionmentioning
confidence: 99%
“…PCV1 has therefore been considered non-pathogenic to pigs. But recently, PCV1 has also been described as pathogenic to porcine foetuses [14].The PCV1 genome consists of a circular single-stranded DNA of 1759 nt [13]. It has a genomic organization similar to that of PCV2, containing two major open reading frames (ORFs): ORF1, which encodes two proteins (Rep and Rep 0 ) that are involved in virus replication [11,12], and ORF2, whose product is the major structural capsid protein.…”
mentioning
confidence: 99%
“…PCV1 has therefore been considered non-pathogenic to pigs. But recently, PCV1 has also been described as pathogenic to porcine foetuses [14].…”
mentioning
confidence: 99%
“…antigen was detected in the fetal myocardium. As only fetal heart tissues were investigated in the current study, the tissue tropism of PCV1-2 is unknown, and PCV1 has been previously identified in fetal lung tissues (20), PCV1-2, although unlikely, could have been present elsewhere in the fetal tissues. As a PCV1-2 chimeric virus was identified in Canadian swine herds, the risks of introduction of a live-attenuated PCV2 vaccine for use in breeding age females needs to be seriously considered before approval.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PCV1 has been associated with hemorrhages in lung tissues of fetuses experimentally inoculated with the PK-15 cell-derived PCV1 isolate but not a field isolate of PCV1 (20).…”
Section: Pcv2 Vaccine Efficacy Under Field Conditionsmentioning
confidence: 99%